IMPLEMENTATION OF A RURAL COMMUNITY-BASED PROGRAM TO IMPROVE PSYCHOLOGICAL WELL-BEING OF OLDER ADULTS - Jennings, L A (Innov Aging, 2018)
The Oklahoma Healthy Aging Initiative’s Healthy Brain Healthy Mind (HBHM) is a 4-week class that addresses the emotional well-being of older adults using an approach sensitive to mental health stigma. Over 3 years, 118 HBHM classes were delivered in 68 communities; 44 classes (37%) completed evaluations (N=193 participants). Most participants were female (81%), aged 60+ (79%), white (54%), and rural-dwelling (52%). Participants completed 21-item Depression Anxiety Stress Scale before and after HBHM. Scores were compared using a paired t-test and showed improvements in all domains: depression, -0.78(SD0.02); anxiety, -0.64(SD0.03), stress -0.77(SD0.04) points; p<0.05). 97% of participants reported HBHM helped them deal with stress; 100% would recommend to others. A subgroup analysis (3 sites, N=31) showed improvement on a 6-item companionship scale (-1.6 points, p=0.02). Community-based education to improve psychological well-being was well received by rural-dwelling older adults, reduced self-reported symptoms of stress, anxiety, and depression, and improved connectedness to others.